Influence of Flash Droughts and High Fuel Prices on Recent Spikes in Grain Barge Rates on the Mississippi River - Lincoln F. Pratson; Ben Foster; Gregory W. Characklis (Water Resources Research, 2025)
Abstract In 2022, 2023 and 2024, flash droughts in the U.S. Midwest caused the lower Mississippi River to drop to record low levels during corn and soybean harvest season. Grain barges that move the crops downriver to New Orleans for export were forced to reduce their loads to avoid grounding. The load reductions and by extension the low river levels have been attributed as the causes for significant spikes in barge spot prices during the droughts, which for the transit from St. Louis, MO to New Orleans, LA climbed from an average pre‐drought maximum of $27/ton to as high as >$105/ton in 2022. A dynamic regression model was developed to test whether the barge rate highs might also be the result of high fuel costs over the same period. Results produced by the model not only support this hypothesis but indicate that the increases in fuel costs were the dominant reason barge rates spiked. The influence of the flash droughts on the other hand was estimated to account for ≤16% of the peak rates. These results are supported by the fact that the rates did not surge during past events when barge loads had to be reduced and shipping was delayed, including during flash droughts in 2012 and 2013.